Estrutura e interações tróficas em três lagoas marginais no Pantanal Sul - MORAIS, Ronny José de (2010)
In this study trophic interactions and flows of energy/matter of three lagoons in the Pantanal (MS) submitted to the annual flood pulse - Baia da Onça, Braço Morto Acima and Braço Morto Abaixo - were analyzed with models of mass balance constructed using the Ecopath software. Thus, the objectives were: (i) to describe the mechanisms that control the dynamics of trophic webs, (ii) to identify the major groups that act as keystone, (iii) to identify information gaps for these environments, (iv) to quantify the ecotrophic community and assess the degree of development of the ecosystem. In addition to several fish compartments in other groups were inserted to compose the models, such as phytoplankton, macrophytes, zooplankton, aquatic insects, terrestrial insects, birds, reptiles and mammals. The data from fish compartments were collected in 1988-1990 and the other compartments were taken from literature. To identify the groups that act as keystone an index that is based on the trophic impact matrix of each model was used. The results indicate that in the three models, biomass and number of species concentrated between trophic levels 2 and 3, suggesting that within these levels there is greater stability, allowing the coexistence of species. In the three models, the most effective contribution of the energy flow is observed from the detritus compartment to the trophic level II, highlighting the role of detritivores in the systems. The trophic impact matrix obtained for the three models confirms the participation of detritus and some compartments found in lower trophic levels (aquatic insects and zooplankton) over most of the groups in the models, suggesting a bottom up control system. However, the presence of top predators and their strong relationships with other groups suggest the presence of top-down effect. This is verified by analysis of the index of keystone, which in the three models is greater for detritus, Hoplias malabaricus, Serrasalmus spp, birds and mammals. So, there are in the three lagoons a matched control (bottom-up and top-down) with the acting of primary producers and higher trophic levels. The analysis of some ecosystem attributes, such as PP/R, Ascendency, Overhead and Ratio Schödinger show that the three systems are mature and have high resilience. This study is considered an initial step in the synthesis of ecological interactions about the Pantanal lagoons (MS) for that there are no studies with this approach to this ecosystem.